Exploring reported causes of vaccine hesitancy among European adolescents and parents: results of a citizen science project - Pere Millat-Martínez; Ana Mora; Pol Ezquerra Condeminas; Miquel Castelló; Claudia Alsina; Beatriz Fiestas; Matteo Bason; Montserrat Esquerda; Alexandre Perera-LLuna; Begonya Nafria; Quique Bassat (BMC Public Health)
Abstract Background Progress in pediatric immunization is threatened by vaccine hesitancy. While recent estimates show 14–35% of European parents exhibit some degree of hesitancy, little is known about adolescents. We assessed vaccine hesitancy and associated factors in European adolescents and parents through the online Science4Pandemics platform. Methods We conducted two cross-sectional surveys. One in individuals aged ≥ 12 and < 18 years, using a non-validated questionnaire adapted from the Parent Attitudes about Childhood Vaccines (PACV); and another using the PACV questionnaire in parents aged ≥ 18 years, who were not necessarily related to the adolescents. Results 1877 adolescents from Italy, Portugal, Poland and Spain were included. Of these, 45.9% were aged 12–14 years, and 54.1% were 15–17 years. The prevalence of hesitancy (adapted PACV score ≥ 50%) was 20.8% (390 individuals). Hesitancy prevalence varied between countries, from 12.5% in Spain to 31.6% in Poland (p < 0.001). Geographic region was the only associated factor for hesitancy [Odds Ratio (OR) for Polish adolescents: 3.20 (95%CI: 2.29, 4.51); OR for Italian adolescents: 2.28 (95%CI: 1.62, 3.24); OR for Portuguese adolescents: 1.13 (95%CI: 0.77, 1.66); all compared to Spanish adolescents]. Country remained the only associated factor in the multivariate logistic regression analysis. In contrast, 1135 parents of children under 18 were included, with hesitancy observed in 20.4% (232 individuals). The main associated factors for hesitancy, both in the univariate and multivariate analyses, were country of residence [OR for Italian parents: 2.34 (95%CI: 1.47, 3.80); OR for Polish parents: 2.69 (95%CI: 1.70, 4.36); OR for Portuguese parents: 2.26 (95%CI: 1.41, 3.68); all compared to Spanish parents], and age, with older parents being less hesitant (OR: 0.97, 95%CI: 0.96, 1.00). In both parents and adolescents, the main reasons for vaccine hesitancy were fear of vaccine side effects (56.1% in adolescents, 51.9% in parents) and lack of trust in government recommendations (21.9% in adolescents, 22.8% in parents). Conclusions Vaccine hesitancy in adolescents and parents in Europe is prevalent, with country of residence as a key influencing factor. Targeted strategies to educate both groups about immunization benefits and its side effects are essential, considering the heterogeneity across countries and reasons for hesitancy.